Effects of cypermethrin on survival, morphological and biochemical aspects of rohu (Labeo rohita) during early development. (February 2016) - Dawar, Farman Ullah; Zuberi, Amina; Azizullah, Azizullah; Khan Khattak, Muhammad Nasir
Abstract: The present study was conducted to investigate the effect of sub-lethal doses of Cypermethrin (CYP) on the survival and morphological and biochemical aspects of rohu ( Labeo rohita ) during early developmental stages. Newly fertilized eggs were incubated in the presence of sub-lethal concentration of CYP (20% of LC50 i.e., 8.43 μg L −1 ) in a well designed flow through system. Increased mortality was found with increase in exposure time. Deformities like eroded yolk and margins, elongated yolk sac, larvae with short tail, no eyes or larvae with zigzag movement and paralyzed larvae were observed in CYP treated group from blastula to fry stage. The activities of antioxidant like Catalase (CAT), Peroxidase (POD) and Lactoperoxidase (LPO) were decreased from 24 to 96 h in the control group whereas increased in CYP treated group. The Glutathione reducatse (GR) activity was also increased with time in both the control and treated groups; however, the activity was significantly higher in CYP treated group. Similarly, the whole body cortisol level showed an increasing trend with time in both control and treated groups. However, in CYP exposed group the cortisol level was considerably higher after 24 h exposure but statistically comparable to the control group after 96 h. It can be concluded from the present results that CYP even at very low concentration adversely affects the early development of L. rohita and enhances mortality. The obtained results reveal that CYP may affect the wild population of fish by inducing oxidative stress and modulating stress response during early ontogenesis. Highlights: The effect of Cypermethrin on Labeo rohita during early developmental stages was studied. Sub-lethal doses of Cypermethrin caused increased mortality and a variety of deformities in fish. Cypermethrin caused an increased oxidative stress in fish. Cypermethrin can affect the wild population of fish by inducing oxidative stress.